A survey of the factors affecting the productivity of construction projects in Iran - Ghoddousi, Parviz; Hosseini, Mohammad Reza (Technological and Economic Development of Economy, 2012)
The intense competition between the Iranian construction companies has led them to take all appropriate measures to decrease the costs as much as possible. Hence, due to the pivotal role of human resources in construction projects cost, a major part of Iranian construction companies seek their profitability and survival in maximizing the productivity of their operatives. Because of the widespread belief among contractors about the low productivity of daily workers and operatives with basic salary, they commit a major part of their projects activities to sub-contractors. Deployment of sub-contractors by construction firms has become largely conventional in country's construction projects. The aims of this paper is defined as determining the factors and grounds affecting sub-contractors productivity and evaluate their overall negative side effects on project productivity via a structured questionnaire. A total of 31 factors selected and were divided into 7 broad categories. The perceptions of companies managers were asked about the level of effect brought about by the mentioned factors and groups upon productivity on a time based criterion. The analysis indicated that the most important grounds affecting sub-contractors productivity in descending order include: Materials/Tools, Construction technology and method, Planning, Supervision system, Reworks, Weather, and Jobsite condition. Project managers should focus on the identified major grounds and relevant factors in order to improve productivity as long as they commit construction activities to sub-contractors.